Spatially resolving the cone of reaction for a single molecule - Matthew James Timm; Adam Matěj; Ilias Gazizullin; Qifan Chen; Stefan Hecht; Pavel Jelínek; Leonhard Grill (Science, 2026)
Collisions of atoms and molecules are required for bond formation and are thus key to any chemical reaction. Their outcome is determined by the collision energy, relative orientation, and impact parameter of the reactants. Collision studies in the gas phase have shown that energies are easily controlled, whereas it is difficult to steer the molecular orientations and completely impossible to control the impact parameter. Here, we study the collision of individual molecules at a surface where each involved compound is imaged before and after collision by scanning tunneling microscopy, allowing precise control of orientations and impact parameter. We observe that the molecules must collide in a narrow cone of reaction and that surface atom displacements can enable a reaction even for disfavored pathways.